2009
DOI: 10.1258/rsmsmj.54.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EUS-FNA in the Management of Patients with Oesophageal Cancer

Abstract: EUS-FNA appears to help direct patients towards appropriate treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…However, a study by Shimpi et al [20] showed that EUS provides good staging accuracy after dilatation of the malignant stricture. Compared with our study where EUS-guided FNA was not performed, recent studies [21,22] with EUS-guided FNA of enlarged lymph nodes showed greater change in the management protocol (50% vs 67%) in patients with oesophageal carcinoma.…”
Section: Discussioncontrasting
confidence: 84%
“…However, a study by Shimpi et al [20] showed that EUS provides good staging accuracy after dilatation of the malignant stricture. Compared with our study where EUS-guided FNA was not performed, recent studies [21,22] with EUS-guided FNA of enlarged lymph nodes showed greater change in the management protocol (50% vs 67%) in patients with oesophageal carcinoma.…”
Section: Discussioncontrasting
confidence: 84%
“…Findings from EUS-FNA have changed the management strategy an additional 8% (95% CI, 6% to 15%) of the cases 6. It was shown, in another study, that EUS-FNA has altered the management strategy in as high as 67% of patients 7. Addition of EUS-FNA to EUS is generally recommended when the histopathologic result of EUS-FNA can influence the diagnosis or choice of therapeutic options.…”
Section: Eus and Eus-fna In Esophageal Cancermentioning
confidence: 99%